Alpha-1 antitrypsin gene exon use in stimulated lymphocytes. Issue 9 (September 1992) - Bashir, M S; Morrison, K; Wright, D H; Jones, D B
Abstract : AIMS: To investigate the expression of mRNA transcripts containing exon A or B in lymphocyte cultures. METHODS: An in situ hybridisation technique, using synthetic, biotinylated oligonucleotide probes was deployed to allow the demonstration of exon A, exon B, or the normal hepatocyte message containing exon C. RESULTS: Lymphocytes used the same alternative splicing technique as monocytes in the generation of their alpha-1 antitrypsin message. They also provided data on the frequency of exon A and B expression in cells from different subjects. Most circulating granulocytes failed to show the alpha-1 antitrypsin message, suggesting that this protein is synthesised in the marrow and represents a stored protein component in polymorph and circulating nuclear lymphocytes. CONCLUSIONS: In situ hybridisation is a sensitive technique for the detection of individual gene exon use in cell populations. Lymphocytes show the same promoter use as that described for monocytes.